ANALYSIS OF FIRE FIGHTING PUMP PERFORMANCE USING SNI 03-6570-2001 STANDARD ON SELF-CONTAINED HYDRANTS - Abdurrahman Auf; Agung Wahyudi Biantoro; Dedik Romahadi; Amat Chaeroni (Universitas Mercu Buana, 2023)
Self-controlled hydrants are fire protection systems located in residential areas that function for early fire extinguishing. In a fire protection system, the pump plays an important role in supplying water from the reservoir to the end point of the installation. Fire pumps must always be in optimum condition and accordance with applicable standards. This study aims to analyze pump performance at current conditions in self-contained hydrants in the Palmerah District and then compare it with the performance that pumps should have in ideal conditions according to SNI 03-6570-2001 standards. The method used is a quantitative descriptive analysis method by comparing the current condition of the pump with applicable standards and conducting a direct survey of the location of the installed fire pump. The measuring instruments used in the study were a pressure gauge, control box, and pitot gauge. The results obtained through testing and calculating pump performance The pump installed on the self-contained hydrant in actual conditions with a total head of 86.62 m produces a flowrate of 0.0189 m3/s at 2800 RPM and can flow a maximum flowrate of 0.0284 m3/s with a head of 66.94 m while in ideal conditions with approximately the same speed and total pump head of 88.83 m, The pump produces a flow rate of 0.0473 m3/s and can produce a maximum flowrate of 0.0710 m3/s with a head of 71.81 m and when shut-off (Q = 0) at actual and ideal conditions produces a same total pump head 94.10 m. However, the pump in actual conditions can flow a minimum flowrate required of 0.040 m3/s with a pressure required of 350 kPa at 3000 RPM with a total pump head of 108.52 m. Thus, the pump must operate heavier due to the higher total head to deliver the required minimum flow rate and pressure.